Reply to the 'Comment on "Elucidation of charge-transfer SERS selection rules by considering the excited state properties and the role of electrode potential"' by M. Mohammadpour, M. H. Khodabandeh, L. Visscher and Z. Jamshidi, Phys. Chem. Chem. Phys., 2017, 19, 7833. Issue 40 (4th October 2017) - Jamshidi, Zahra; Khodabandeh, Mohammad Hassan; Mohammadpour, Mozhdeh; Visscher, Lucas
Abstract : The role of electrode potential in the amount of charge-transfer, stability of metal-pyridine and pattern of SERS spectra is investigated. Abstract : We appreciate Aranda's comments on our recent work entitled ''Elucidation of charge-transfer SERS selection rules by considering the excited state properties and the role of electrode potential''. We would also like to thank the editor of Physical Chemistry Chemical Physics for giving us an opportunity to specify more details of our work in this reply. An important part of our article concerns the role of the electrode potential in charge-transfer SERS spectra and we would like to first address the questions that Aranda et al. posed about our labeling.